Analysis of risk factors for postoperative recurrence of stage IA lung adenocarcinoma - Xu, Wendong; Li, Runze; Tuerxun, Dilihumaer; Wang, Yuanguo; Li, Jian; Li, Jingyu; Zhang, Peng (Frontiers in Oncology, 2025)
ObjectiveTo explore the influencing recurrence in patients with stage IA lung adenocarcinoma following surgical resection.MethodA retrospective analysis was conducted on the clinical and pathological data of patients with stage IA lung adenocarcinoma who underwent surgical resection in the Department of Thoracic Surgery at Tianjin Medical University General Hospital from January 1, 2018, to December 31, 2021. The Fine-Gray model was utilized for multivariate analysis to identify factors influencing the cumulative incidence of lung cancer recurrence. The hazard ratio (HR) and its 95% confidence interval (CI) were calculated.ResultAmong 475 patients, there were 30 cases of postoperative recurrence and metastasis. The results of the univariate analysis using the Gray test indicated that vascular invasion, STAS, solid and micropapillary patterns, pTNM classification, lymph node resection method, surgical method, organizational differentiation, CTR had a significant impact (P<0.05). The multivariate analysis revealed that pTNM classification, lymph node resection method, vascular invasion and the presence of solid or micropapillary patterns were significantly correlated.ConclusionTumor staging, the presence of solid or micropapillary components in pathology, vascular invasion, and the method of lymph node resection significantly influence postoperative disease-free survival (DFS) in patients with stage IA lung adenocarcinoma undergoing surgical resection.